Nudging the agents: Does it reduce discrimination against migrants in the house rental market? - Wladimir Zanoni; Lina Díaz; Emily Díaz; Jorge Paredes; Paloma Acevedo (Inter-American Development Bank (IDB), 2023)
This study examines the impact of a behavioral intervention on reducing discrimination against Venezuelan migrants in the screening of home rental applications conducted by Ecuadorian real estate agents (REAs). Given that Venezuelan migrants represent the second-largest migratory group globally, with over seven million individuals seeking refuge primarily in other Latin American countries, understanding and addressing discrimination against them is of significant importance. Our artifactual field experiment involved providing information to REAs that highlighted the extra efforts Venezuelan migrants must make to achieve the same goals as nonmigrants in host countries. The results demonstrated a meaningful increase of 33.67% in the preference for Venezuelan migrants over native applicants, with this effect mainly driven by changes in male REAs discriminatory behaviors. The findings suggest that challenging the information value of Venezuelan migrant stereotypes, which often underlie assumptions about their qualities, can effectively diminish discrimination during the rental application process. This research contributes valuable insights to the ongoing efforts to identify effective means to deal with discrimination against migrants.
Keywords: F22; J15; R31; 330; Field experiments; Behavioral Interventions; Nudges; Migration; Prejudice